Thump, thump, rat-a-tat-tat - Baer, Gene, 1927-; Ehlert, Lois (New York : Harper & Row, 1989)
A distant marching band grows larger and louder as it nears, and then softer and smaller as it goes away again.
"A Charlotte Zolotow book."
Children's Catalog (Wilson)
*BOOKLIST*
*Horn Book*
1.8
K-3
Keywords: Bands (Music) -- Fiction; Sound -- Fiction; Bands (Music) -- Fiction; Sound -- Fiction